ANALISIS KEMAMPUAN BERKOMUNIKASI SISWA SMA MELALUI POSTER HASIL PRAKTIKUM PADA SUBKONSEP PENCEMARAN TANAH - Adang, Annisa Hafitasari (2013)
Study to analyze the High School student's (SMA) communication skills in soil pollution subconcepts based learning through guided inquiry lab (guided inquiry). The method used is descriptive method. The research was conducted on the subjects of Biology at one high school in Bandung school year 2012/2013 in the second semester. Study subjects consisted of 52 students class in the two studies. The data obtained in this study is the ability to communicate through a poster of data lab results, student response data for making posters based on lab results and response instructors (teachers). Based on the data analysis and discussion in this study found that students' ability to communicate the results in a poster practicum lab results categorized quite well. Communication skills of students in 12 predetermined indicators assessment sequence showing the sequence of student mastery of the highest to the lowest element of completeness, practical purpose, beauty and timeliness, conclusions, read the plot, graphs, tables, reference sources, methods, image or photo lab results , discussion, and preliminary (background). Most of the students responded positively about making posters lab results and its ability to communicate and form of soil contamination subconcepts learning through guided inquiry lab she lived. Keywords: Ability to communicate, posters lab results, ground pollution subconcepts, analysis Studi untuk menganalisis kemampuan berkomunikasi siswa Sekolah Menengah Atas (SMA) pada subkonsep pencemaran tanah dilakukan melalui pembelajaran berbasis praktikum. Metode penelitian yang digunakan adalah metode deskriptif. Penelitian ini dilaksanakan pada mata pelajaran Biologi di salah satu SMA di Kota Bandung tahun pelajaran 2012/2013 pada semester genap. Subyek penelitian terdiri dari 52 orang siswa/i pada dua kelas penelitian. Data yang diperoleh dalam penelitian ini adalah data kemampuan berkomunikasi melalui poster hasil praktikum, data angket siswa serta tanggapan pengajar (guru). Berdasarkan analisis data dan pembahasan dalam penelitian ini ditemukan bahwa kemampuan siswa dalam mengomunikasikan hasil praktikum dalam poster hasil praktikum termasuk kategori cukup baik dengan rata-rata persentase penguasaan sebesar 64,4%. Kemampuan siswa dalam menyajikan poster sesuai dengan dua belas indikator berada pada rentang kategori sangat baik, sedangkan kemampuan siswa dalam menyajikan poster hasil praktikum dengan tepat waktu berada dalam rentang kategori baik.. Sebagian besar siswa merespon positif tentang pembuatan poster hasil praktikum dan kemampuan berkomunikasi yang dimilikinya serta bentuk pembelajaran subkonsep pencemaran tanah melalui praktikum yang dijalaninya. Kata kunci: Kemampuan berkomunikasi, poster hasil praktikum, subkonsep pencemaran tanah, analisis